Swelling Properties of Poly(N-isopropylacrylamide)/Calcium Alginate Interpenetrating Polymer Network Hydrogel containing Zirconia - Hong Ooi, Ing; Hui Ng, Shi; Kie Chong, Yie; Kiat Wong, See (Asian Journal of Chemistry, 2015)
Temperature-responsive poly(N-isopropylacrylamide)/calcium alginate interpenetrating polymer network hydrogels contaning different percentages of zirconia were prepared and evaluated for their swelling properties. The pore size of the interpenetrating polymer network hydrogels decreased with increasing content of zirconia. Incorporation of zirconia into the interpenetrating polymer network hydrogel decreased its ability to swell at temperatures below its lower critical solution temperature but resulted in larger shrinkages at temperatures above its lower critical solution temperature. The swelling-deswelling behaviour of the interpenetrating polymer network hydrogels between 25 °C and 37 °C was, however, rapid, responsive and reproducible.